2019
DOI: 10.1371/journal.pone.0214715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a progressive stepped care approach in an improving access to psychological therapies service: An observational study

Abstract: England’s national Improving Access to Psychological Therapies (IAPT) programme advocates stepped care as its organizational delivery of psychological therapies to common mental health problems. There is limited evidence regarding the efficacy of stepped care as a service delivery model, heterogeneity of definition and differences in model implementation in both research and routine practice, hence outcome comparison in terms of effectiveness of model is difficult. Despite sound evidence of the efficacy of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Interestingly, Gyani et al (2013) found that IAPT services with a higher step-up rate also had a higher recovery rate, highlighting some potential for utilizing a stepped-care system that encouraged patients to continue from low-to high-intensity work where appropriate. Moreover, Boyd et al (2019) highlight that following a stepped-care progression model, rather than a stratified model, was associated with more reliable recovery rates. They suggested that individuals who were more severely depressed benefitted from receiving simpler, more structured elements of CBT (e.g., behavioural activation).…”
Section: Does Iapt's Stepped-care Treatment Model Prevent Transition To Secondary Care Services?mentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, Gyani et al (2013) found that IAPT services with a higher step-up rate also had a higher recovery rate, highlighting some potential for utilizing a stepped-care system that encouraged patients to continue from low-to high-intensity work where appropriate. Moreover, Boyd et al (2019) highlight that following a stepped-care progression model, rather than a stratified model, was associated with more reliable recovery rates. They suggested that individuals who were more severely depressed benefitted from receiving simpler, more structured elements of CBT (e.g., behavioural activation).…”
Section: Does Iapt's Stepped-care Treatment Model Prevent Transition To Secondary Care Services?mentioning
confidence: 87%
“…Outcomes in the stepped-care model Seven papers reported on the utility of the IAPT stepped-care model. One study compared the progressive model (step-by-step) with a stratified model (assessment then assigned to the appropriate treatment step), reporting that recovery was associated with the former where most service users received Step 2 (low-intensity) treatment only (Boyd, Baker, & Reilly, 2019). Another identified that services with a higher 'step-up' rate also had overall higher reliable recovery rate (Gyani, Shafran, Layard, & Clark, 2013).…”
Section: Competenciesmentioning
confidence: 99%
“…Since 2008, services under the IAPT programme have offered evidence-based psychological interventions to individuals with common mental health difficulties (anxiety disorders and depression) across England (Clark, 2011). These interventions, which have been predominantly CBT orientated, are delivered in line with guidance from the National Institute for Health and Care Excellence (NICE) that advocates a stepped-care model of service delivery, which has been shown to allow services to see more patients in a manner that is clinically and cost effective (NICE, 2011;Boyd et al, 2019). As part of this model, a range of high-intensity interventions are recommended that have expanded beyond CBT to include Interpersonal Therapy (IPT), Couples Therapy, Dynamic Interpersonal Therapy (DIT) and Counselling for Depression (CfD), as well as Eye Movement Desensitisation Re-processing therapy (EMDR) for PTSD (NICE, 2018).…”
Section: The Role Of Iapt Servicesmentioning
confidence: 99%
“…Although evidence for the cost-effectiveness of stepped care is scarce, services that deliver care in a progressive delivery model have been shown to achieve better outcomes than services with a stratified treatment model. 10 We therefore endorse the stepped care principles, although more research is warranted. In summary, Vedaa and colleagues' study shows that large effects can be achieved through SHUTi, and adds to the compelling evidence for dCBT-I.…”
mentioning
confidence: 92%